Study on Anti-fatigue Effect and Mechanism of Angelica sinensis Polysaccharide - HUANG Caiyun; HE Jifu; SONG Chunhong; WANG Nan; MA Yude (康复学报)
ObjectiveTo investigate the anti-fatigue effect and mechanism of Angelica sinensis polysaccharide (ASP) at di-fferent doses in mice.MethodsA total of 50 SPF male Kunming mice were randomly divided into blank control group, model group, ASP high-dose group, ASP medium-dose group, and ASP low-dose group according to the random number table method, with 10 mice in each group. Except for the blank control group, mice in each group carried out loaded swimming to exhaustion once a day for 15 days. From the 6th day of modeling, mice in the ASP high-dose group, medium-dose group and low-dose group were intragastrically administered with corresponding doses of ASP (222.56, 111.28, 55.64 mg/kg), respectively, while mice in the blank control group and model group were given the same amount of normal saline by intragastric administration for 10 days. The time taken for loaded swimming to exhaustion in the last day was recorded, and the exercise endurance was evaluated. Then the specimens were gathered, the serum muscle glycogen, liver glycogen, blood lactic acid and blood urea nitrogen were detected, and the content of ATPase in liver, kidney and hindlimb muscle was detected.Results1) Compared with the model group, the swimming time of mice in the ASP medium-dose group and ASP high-dose group was prolonged (P<0.05); compared with the ASP low-dose group and ASP medium-dose group, the ASP high-dose group showed longer loaded swimming time (P<0.05). 2) Compared with the blank control group, the serum muscle glycogen and liver glycogen content of mice in the model group decreased (P<0.05); compared with the model group, the serum liver glycogen content of mice in the ASP medium-dose group increased (P<0.05), and the serum muscle glycogen and liver glycogen content of mice in the ASP high-dose group increased (P<0.05), and the serum muscle glycogen content of mice in the ASP high-dose group had the most significant increase (P<0.05). 3) Compared with the blank control group, the serum blood lactic acid and urea nitrogen content of mice in the model group increased (P<0.05); compared with the model group, the serum blood lactate content of mice in the ASP low-dose group decreased (P<0.05), and the serum blood lactate and blood urea nitrogen content of mice in the ASP medium-dose group and ASP high-dose group decreased (P<0.05), with the most significant decrease shown in the serum blood lactic acid content of mice in the ASP high-dose group (P<0.05). 4) Compared with the blank control group, the Na+-K+-ATPase and Ca2+-Mg2+-ATPase in liver of mice in the model group decreased (P<0.05), the Na+-K+-ATPase, Mg2+-ATPase and Ca2+-Mg2+-ATPase in kidney decreased (P<0.05), and the Na+-K+, Mg2+, Ca2+ and Ca2+-Mg2+ ATPase in hindlimb muscles of mice in the model group decreased (P<0.05). Compared with the model group, the Ca2+-Mg2+-ATPase in hindlimb muscles of mice in the ASP low-dose group increased (P<0.05). The Ca2+-Mg2+-ATP in liver of the mice in the ASP medium-dose group significantly increased (P<0.05), the Mg2+-ATPase, Ca2+-ATPase and Ca2+-Mg2+-ATPase in hindlimb muscle significantly increased (P<0.05), the Na+-K+-ATP and Ca2+-Mg2+-ATPase in liver significantly increased (P<0.05), and the Na+-K+-ATPase and Mg2+-ATPase in kidney significantly increased (P<0.05). The Na+-K+, Mg2+, Ca2+ and Ca2+-Mg2+ ATPase in hindlimb muscle increased (P<0.05). The increase of liver Ca2+-Mg2+ ATPase of the mice in the ASP high-dose group was the most obvious (P<0.05).ConclusionASP can significantly prolong the loaded swimming time of mice to a certain extent and play an anti-fatigue effect. The underlying mechanism is related to the fact that ASP can significantly improve the exercise endurance, increase glycogen reserve, reduce the accumulation of lactic acid and urea nitrogen, and improve energy metabolism of mice.